THE EFFECT OF DEBT TO EQUITY RATIO (DER), CURRENT RATIO (CR), AND GROWTH ASSETS ON DIVIDEND POLICY IN CONSUMER GOODS MANUFACTURING COMPANIES WHICH IS LISTED IN THE STOCK EXCHANGE INDONESIA 2015-2017 PERIOD - Jasinta Mustika Sianipar (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2020)
The existence of this study is to determine the effect of DER, CR, and AG on the consumer goods sector dividend policy contained on the IDX. Research is classified as a quantitative approach, the type of research used is quantitative descriptive and its nature is based on the level of explanation. The population is 50 companies and the sample is 19 companies. Data collection techniques are documentation and sources of IDX financial statements. This research is tested using multiple linear regression methods before testing the hypothesis the data will be tested using the classic assumption test. The conclusions obtained in the study showed that simultaneously DER, CR, and AG had a positive influence on dividend policy. Partially, DER has a positive and significant impact on dividend policy with a value of 2,792> 1.67412 and 0.008 <0.05. CR positive and significant effect on dividend policy 2,780> 1.67412 and 0.008 <0.05. AG negative and insignificant effect 2.780> 1.67412 and significant value 0.436> 0.05.Keywords: Debt To Equity Ratio (Der), Current Ratio (Cr), And Asset Growth (AG) Against Dividend Policy